Quality of Service: Traffic prioritization (Zien Journal of Social Sciences and Humanities, 2022)
In this article, we will see what Quality of Service is, its parameters and tasks, the principle of operation, traffic prioritization, and at the same time how its main work is carried out. QoS traffic prioritization technology will help ensure the smooth transmission of data that is of paramount importance.